Hi Harris
x²=6x-9
First thing we need to do is
subtract 6x-9 from the booth sides
x²-(6x-9)=6x-9-(6x-9)
x²-6x+9=0
Now we gonna factor the left side
(x-3)(x-3)=0
Set factor equal 0
x-3=0 or x-3=0
x=3
I hope that's help !
x² = 6x - 9, or x² - 6x + 9 = 0, or x² - 2*x*3 + 3² = 0, or (x-3)² = 0 => x₁ = x₂ = 3.
Green eyes.
Answer:
Step-by-step explanation:
In triangle if two sides are known and included angle is known we can use cosine formula as follows:
Say in a triangle, sides a,b are known and also included angle C
Then the third side
Since all values on right side are known, we can find the third side c easily.
Case II:
If alternately two sides and one angle not included is known. i.e we know a,b and either angle A or B.
then to find third side we use sine formula.
Using the above we can find the unknonwn side c easily.
0 1
02
O 10
O 30
The value of n which makes the exponential value equation true is n = 10
When you raise a quotient to a power you raise both the numerator and the denominator to the power. When you raise a number to a zero power you'll always get 1. Negative exponents are the reciprocals of the positive exponents.
The different Laws of exponents are:
mᵃ×mᵇ = mᵃ⁺ᵇ
mᵃ / mᵇ = mᵃ⁻ᵇ
( mᵃ )ᵇ = mᵃᵇ
mᵃ / nᵃ = ( m / n )ᵃ
m⁰ = 1
m⁻ᵃ = ( 1 / mᵃ )
Given data ,
Let the exponential equation be A
Now , the value of A is
A = ( 2x⁹yⁿ ) ( 4x²y¹⁰ ) = 8x¹¹y²⁰
So , from the laws of exponents , we get
mᵃ×mᵇ = mᵃ⁺ᵇ
( 2x⁹yⁿ ) ( 4x²y¹⁰ ) = 8x⁹⁺²yⁿ⁺¹⁰
( 2x⁹yⁿ ) ( 4x²y¹⁰ ) = 8x¹¹yⁿ⁺¹⁰
And , the value of A is = 8x¹¹y²⁰
So , on simplifying , we get
8x¹¹y²⁰ = 8x¹¹yⁿ⁺¹⁰
y²⁰ = yⁿ⁺¹⁰
Since the bases are same , the powers are also same
20 = n + 10
Subtracting 10 on both sides , we get
n = 10
Hence , the exponential equation is solved and n = 10
To learn more about exponents click :
#SPJ7
Answer:
02
Step-by-step explanation:
30is the beginning answer
Answer:
(x+2)(x-3)
Step-by-step explanation:
easy